Dietary methionine requirement of juvenile arctic charr, Salvelinus alpinus - Simmons, Alfred Lincoln Arthur (University of Guelph, 1997)
The dietary methionine requirement of juvenile arctic charr was determined by feeding a basal diet supplemented with six graded levels of DL-methionine for 16 weeks at 12$\sp°$C. All diets contained 40% protein, 77% lipid, 6.6% ash and 17.5 MJ DE/kg of diet. As evaluated by live weights, the methionine requirement for optimal growth is 1.76% of dietary protein, estimated by the quadratic regression model. This is the same value predicted by a dynamic computer model developed for arctic charr. Requirements estimated on the basis of carcass protein and energy gains are 1.88% and 1.79% respectively. Plasma methionine concentration and focal length variability measurements did not provide a sensitive measure of requirement as each responded in a linear fashion to increasing dietary methionine levels. Based on the prevalence of visually detectable cataracts, it is estimated that a dietary methionine level of 2.67% is required to prevent lens pathology in farmed arctic charr.